A prospective cohort study on the association between ear drop use and otomycosis: prevalence, treatment outcomes, and recurrence - Mizhir Almaamuri, Abdulhusein (Pharmakeftiki, 2025)
This study investigates the incidence of otomycosis associated with ear drop usage and evaluates treatment outcomes and recurrence rates in Iraqi patients with and without a recent history of ear drop application. Conducted at the ENT Clinic of Almahawil Hospital (Iraq) from April 1, 2022, to March 31, 2024, the study involved 280 patients diagnosed with otomycosis. Participants were divided into two groups: group 1 (N=72) comprised individuals who had used ear drops within 1–2 weeks prior to diagnosis, while group 2 (N=208) comprised individuals who had not recently used ear drops. Our findings revealed that 26% of otomycosis cases were linked to recent ear drop use, with ciprofloxacin being the most commonly used agent (61.1%). Both groups demonstrated high rates of symptom resolution following treatment; however, the recurrence rate was notably higher among ear drop users (11.1%) compared to non-users (7.8%). These results suggest that ear drop usage may elevate the risk of developing otomycosis and increase the likelihood of recurrence, thereby highlighting the need for judicious prescribing practices.